Production of rigid polyurethane foams using polyol from liquefied oil palm biomass: Variation of isocyanate indexes - Umar Adli, Amran; Kushairi, Mohd Salleh; Sarani, Zakaria; Rasidi, Roslan; Chin, Hua Chia; Sharifah Nabihah, Syed Jaafar; Mohd Shaiful, Sajab; Marhaini, Mostapha (MDPI, 2021)
Development of polyurethane foam (PUF) containing bio-based components is a complex process that requires extensive studies. This work reports on the production of rigid PUFs from polyol obtained via liquefaction of oil palm empty fruit bunch (EFB) biomass with different isocyanate (NCO) indexes. The effect of the NCO index on the physical, chemical and compressive properties of the liquefied EFB-based PUF (EFBPUF) was evaluated. The EFBPUFs showed a unique set of properties at each NCO index. Foaming properties had affected the apparent density and cellular morphology of the EFBPUFs. Increasing NCO index had increased the crosslink density and dimensional stability of the EFBPUFs via formation of isocyanurates, which had also increased their thermal stability. Combination of both foaming properties and crosslink density of the EFBPUFs had influenced their respective compressive properties. The EFBPUF produced at the NCO index of 120 showed the optimum compressive strength and released the least toxic hydrogen cyanide (HCN) gas under thermal degradation. The normalized compressive strength of the EFBPUF at the NCO index of 120 is also comparable with the strength of the PUF produced using petrochemical polyol.